Sexual sensation seeking, hookups, and alcohol consumption among first-year college students. Issue 8 (17th November 2021) - Thorpe, Shemeka; Ware, Samuella; Tanner, Amanda E.; Kugler, Kari C.; Guastaferro, Kate; Milroy, Jeffrey J.; Wyrick, David L.
Abstract: Objective: To explore sexual sensation seeking (SSS) among an ethnically-diverse sample of first-year college students and their hookup behaviors. Participants: 1, 480 first-year college students who hooked up in the last 30 days were recruited from four universities in 2016. Methods: Students completed an online survey before completing an online STI and alcohol prevention intervention. Results: Male and sexual minority students had significantly higher SSS scores compared to female and heterosexual students respectively. Students with higher SSS scores were less likely to report condom use at last vaginal and anal hookup, more likely to hookup under the influence of alcohol and participate in a wide range of sexual behaviors. There were no significant mean differences in SSS scores by level of intoxication during their last hookup. Conclusion: These findings highlight the role of SSS in predicting sexual risk behaviors of first-year college students and the overall low SSS scores among this sample.